Ciceros Vorschlag zur Güte: libertatis species - Ryan, F. X. (Gerión. Revista de Historia Antigua, 2005)
With a proper understanding of the expression libertatis species, a hitherto opaque reform proposal of Cicero becomes pellucid, and at the same time the experienced polemicist ceases to make an unacceptably unpersuasive argument and begins to make one which is both suitably cogent and wonderfully deceptive.